Molten Salt Strategy for Reproducible Evaporation of Efficient Perovskite Solar Cells. (20th December 2022) - Li, Hang; Tan, Liguo; Jiang, Chaofan; Li, Minghao; Zhou, Junjie; Ye, Yiran; Liu, Yue; Yi, Chenyi
Abstract: Vacuum evaporation is promising for the scalable fabrication of perovskite solar cells (PSCs). Nevertheless, the poor thermal conductivity of metal halide powder leads to unfavorable temperature inhomogeneity, which destabilizes the evaporation rate, posing a major challenge to the reproducible deposition of perovskite films, particularly by coevaporation. Herein, a molten salt strategy is reported for sequentially vacuum evaporation of PSCs. The molten salt increases the thermal conductivity of metal halides and greatly homogenizes the temperature, which stabilizes the evaporation rate and the composition of the resulting perovskite films. The PSCs yield power conversion efficiencies (PCEs) of ≈24% with exceptional reproducibility. The unencapsulated PSCs maintain 85% of the initial PCE after 3600 h of maximum power point tracking and maintain 85% of the initial PCE after being heated at 60 °C for 3000 h. The molten salt strategy opens a new avenue for the application of evaporation in perovskite optoelectronics. Abstract : Molten salt strategy enables the fabrication of perovskite solar cells by two‐step sequential vacuum evaporation with exceptional reproducibility. The PSCs yield power conversion efficiencies of ≈24% and have good operational stability and shelf‐life stability. The strategy has good expansibility in fabricating PSCs with tunable bandgaps.